(untitled) (City Dental College Journal, 2018)
Aims: The study was carried out among 120 dentists working in the selected hospitals of Dhaka city to find out the preventive practice on hepatitis B virus (HBV) infection. Methods: A descriptive type of cross-sectional study was carried out involving 120 dentists working in the selected hospitals of Dhaka city from December 2011 to March 2012 to quantify the preventive practice on HBV infection through a pretested semi-structured questionnaire. Results were analyzed by using the software SPSS 16.0 version (Chicago). Then analyzed data were presented according to the variables of the study showing percentage relationship between variables using appropriate statistical method. Results: Mean age of the dentists was 26.43±6.29 (range, 25-45) years where 74.17% were male and 25.83% were female. Among 120 respondents, 20.83% obtained BDS degree along with a postgraduate training (PGT) in any of the respective fields of dentistry. Others obtained MS in dentistry (21.67%), MPH in dentistry (10.83%), PhD in dentistry (9.17%), DDS in dental surgery (10%) and FCPS in dentistry (6.67%). Academic positions of the respondents were 33.33%, assistant professors, 26.67% associate professors, 19.17% medical officers, and 17.5% were lecturers. Majority (93.3%) dentists knew about HBV transmission, prevention, symptoms, risks, and concurrences. Out of them, 87.5% reported having been tested for HBV which was associated with their designations (p=0.013) and more than 75% reported having been vaccinated against HBV. Conclusions: A high level of knowledge and attitude towards practice in the prevention of HBV was found to be very good among the dentists of Dhaka city though seemed it was not always possible to take precaution for handling emergency patients. Further broad scale studies would be needed to have decisive results. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13831 City Dent. Coll. J Volume-10, Number-1, January-2013